University of the Philippines Institute of Library Science - Integrated Set of Information Sytems (UPILS-ISIS) - Reside, Marie Desiree H.; Cruz, Ma. Divina P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
The University of the Philippines Main Library started to automate its card catalog using CDS/ISIS in 1986. CDS/ISIS was distributed to the other unit libraries on the same year, which the Institute of Library Science (ILS) Library is a part. The ILS Library began to use WINISIS version 1.3 since its release in 1999. Its CDS/ISIS database was imported to use WINISIS.
At present, the ILS Library is using WINISIS version 1.4 (build 19)The objectives of this study is to determine what modules are needed by the ILS Library in an Integrated Library Software, to find out the necessary fields in the creation of an Integrated Library Software for the ILS Library, to find out what features of Library Automation Management Program (LAMP) and Integrated Library Management System (LIS) meet the needs of the ILS Library, and to document the development of the University of the Philippines Institute of Library Science - Integrated Set of Information Systems (UPILS-ISIS) software and to assess the software package's acceptability, functionality, and usability.
The study was undertaken in three phases namely, the Systems Analysis and Design (SAD) Phase, the Software Development Phase, and the Evaluation Phase. The features of UPILS-ISIS were derived from some of the features of the LAMP and LIS software packages, interviews with the library staff, and direct observation of library transactions at the ILS Library. UPILS-ISIS software development was accomplished primarily using WINISIS. Visual Basic 6.0 was used to create the embedded programs for fines computation. Testing and debugging came after the source code was written. The software was tested at the ILS Library for a month.
A comments logbook was left to gather feedback from the library staff. The software package was modified based on the suggestions of ILS Library staff. After which, it was demonstrated to the LIS 260 and LIS 232 masteral students of the University of the Philippines Institute of Library Science. An open forum took place after the demonstration. Questionnaires containing certain criteria for the evaluation of the software package were distributed to the masteral students. These criteria are User Friendliness, Overall Functionality, Screen Design, and Navigation between Modules. The software package rated high on the overall functionality and navigation between modules criteria, but it rated low on the user friendliness and screen design criteria.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Integrated library systems (Computer systems).; WINISIS